Analysis of Financial Management in public Emergency Medical Services sector: Case study of the Department of Emergency Medical Services, Uganda - Kavuma, Peter; Turyakira, Peter; Bills, Corey; Kalanzi, Joseph (African Journal of Emergency Medicine, 2020)
The purpose of the study was to critically analyse financial management of the public Emergency Medical Services (EMS) sector with specific focus on the financing methods for public EMS. Methods: The study is a descriptive cross-sectional quantitative survey. It was conducted in the Department of EMS at the Ministry of Health, Uganda. A census was conducted for all twenty-one members of the Department of EMS. Data was collected with the use of a structured questionnaire. Results: The prominent sources of funding towards EMS in Uganda included government, development partners and charity organizations. The most highlighted factors constraining financial management of EMS included reduced government funding, bureaucracies within government agencies and increasing costs of running EMS. The major strategies to improve on the financial constraints included formation of a national insurance scheme, increasing government's contribution and forming Public-Private Partnerships. Conclusion: The department seemed to be taking on the trend of the developed world in form of strategies to combat financial management constraints which is a step in the right direction but should be cognizant of the challenges this could bring on due to adaptation of these practices. The department of EMS still had a narrow scope of funding sources mainly circling around government and development partner support and was utilizing less of the more contemporary sources mainly exercised by the developed world.
Keywords: Financial Management; Emergency Medical Services